Analysis of students conceptions on the kinetic theory of gases using the Three-Tier test - Muh Arfah; Reski Idamayanti; Agussalim; Napsawati; Syamsuriana Basri (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2026)
This study aims to analyze students' conceptions of the kinetic theory of gases using the Three-Tier Test as a diagnostic instrument. A qualitative descriptive approach was employed involving 15 twelfth-grade students of MA Darussalam Barandasi in the 2025/2026 academic year. Data were collected using a Three-Tier diagnostic test consisting of answer selection, reasoning, and confidence level, and were analyzed using a response-combination rubric. The results show that most students demonstrated adequate conceptual understanding, particularly regarding the relationship between temperature and the kinetic energy of gas particles (13.33%) and the ideal gas law (33.33%). However, misconceptions were identified in the relationship between kinetic energy and gas pressure, the interpretation of gas-law graphs, and the application of the ideal gas law. These findings indicate that abstract concepts remain challenging despite students' relatively good basic understanding. The Three-Tier Test effectively identified hidden misconceptions and provided a comprehensive profile of students' conceptual understanding, making it a useful diagnostic tool for improving physics instruction.